The Impact of Digital Transformation on Tourism and Hospitality in Georgia - Meladze, Maia; Khakhubia, Nino (European Scientific Journal, ESJ, 2025)
Digital technology is the trend nowadays, and it is almost impossible for companies to be competitive in the market without using digital technologies. In recent years, the tourism and hospitality sector has gained immense popularity. The digital products market has appeared with applications that help the hospitality sector be more flexible and effective. Nowadays, many applications and software are created to help business owners control their businesses and satisfy their customers. With the help of Artificial Intelligence software and applications, the business management process is more complex and flexible and allows hotels to be more customer-oriented. Digital travelers themselves are actively using digital applications while traveling. They are searching to download apps that will help them make the reservation process more flexible and more oriented to their wants and needs. The article aims to study the current situation, challenges, and trends of using digital technologies in the hospitality sector of Georgia, to study current applications and software programs, to find and study Georgian tourism and hospitality market representatives, and to interview them. The article highlights the problems and needs that businesses are facing. A qualitative research method was used to study applications and software enterprises use, and a quantitative research method was used to study how digital transformation has affected their businesses. As a result, the research showed that in Georgia, in addition to international tools, local digital products are created and widely used.